Glycosaminoglycans analogs from marine invertebrates: structure, biological effects, and potential as new therapeutics - Pavão, Mauro S. G. (Frontiers in Cellular and Infection Microbiology, 2014)
In this review, several glycosaminoglycan analogs obtained from different marine invertebrate are reported. The structure, biological activity and mechanism of action of these unique molecules are detailed reviewed and exemplified by experiments in vitro and in vivo. Among the glycans studied are low-sulfated heparin-like polymers from ascidians, containing significant anticoagulant activity and no bleeding effect; dermatan sulfates with significant neurite outgrowth promoting activity and anti-P-selectin from ascidians, and a unique fucosylated chondroitin sulfate from sea cucumbers, possessing anticoagulant activity after oral administration and high anti P- and L-selectin activities. The therapeutic value and safety of these invertebrate glycans have been extensively proved by several experimental animal models of diseases, including thrombosis, inflammation and metastasis. These invertebrate glycans can be obtained in high concentrations from marine organisms that have been used as a food source for decades, and usually obtained from marine farms in sufficient quantities to be used as starting material for new therapeutics.